" The phenomenon of political instability in Libya after the political change in 2011 Study: On the causes and requirements" (Tikrit Journal For Political Science, 2024)
AbstractIn belief in the revolution of February 17, 2011, which was led by the Libyan people in various parts of the country, in fulfillment of the souls of the martyrs of this blessed revolution, who sacrificed their lives for freedom, to live in dignity on the homeland, and to restore all the rights that Gaddafi took away from his fallen crime. Boxing theories/traditional political patterns based on the country’s history and based on the legitimacy of this revolution, and responding to the desire and aspirations of the Libyan people to achieve democracy and establish the principles of political pluralism for their benefit, and aspiring to a society that enjoys stability,